2023
DOI: 10.3390/su151612385
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Health Financing among the BRICS: A Literature Review

Abstract: Despite economic progress, government efforts, and increased healthcare investments, health deprivation continues to persist in the countries of Brazil, Russia, India, China, and South Africa (BRICS). Hence, addressing the growing demand for health financing in a sustainable way and adopting unique approaches to healthcare provision is essential. This paper aims to review publications on the existing health financing systems in the BRICS countries, analyze the core challenges associated with health financing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 92 publications
(113 reference statements)
0
0
0
Order By: Relevance
“…This study showed that the lack of motivation among healthcare providers to implement KMC mainly stemmed from the economic unprofitability of departments and hospitals. In the market-oriented healthcare environment in China, hospitals need to be responsible for their own profits and losses, which means they are financially self-sufficient ( 47 , 48 ). When deciding whether to implement a program or procedure, they needed to conduct a cost-benefit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the lack of motivation among healthcare providers to implement KMC mainly stemmed from the economic unprofitability of departments and hospitals. In the market-oriented healthcare environment in China, hospitals need to be responsible for their own profits and losses, which means they are financially self-sufficient ( 47 , 48 ). When deciding whether to implement a program or procedure, they needed to conduct a cost-benefit analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ecevit et al (2023) revealed that population ageing increasingly impacts public health spending in developing economies. Likewise, Sahoo et al (2023) submitted that the ageing population is responsible for rising public health outlay in BRICS countries. Similarly, Aydin and Bozatli (2023) applied a fourier-based analysis in reporting an accelerating effect of refugee population growth on health outlay for Turkey.…”
Section: Empirical Reviewmentioning
confidence: 99%